Past and present of antiobesity agents: Focus on monoamine modulators - Khorassani, Farah E.; Misher, Anne; Garris, Shauna (American journal of health-system pharmacy, 2015)
PURPOSE.A review of recently approved antiobesity medications, including their neuropharmacology, efficacy data from clinical trials, and important patient safety considerations, is presented. SUMMARY.Obesity affects roughly 34% of Americans and is associated with increased risks of type 2 diabetes, hypertension, and coronary artery disease, as well as increased mortality and healthcare costs. Most pharmacologic agents used to treat obesity work by modulating monoamine neurotransmitters such as serotonin, norepinephrine, and dopamine. Since the U.S. market withdrawal of agents such as fenfluramine, dexfenfluramine, and sibutramine due to safety concerns, the Food and Drug Administration (FDA) has approved three monoamine modulators for longterm obesity managementthe serotonergic agent lorcaserin (approved by FDA in 2012), a combination product containing phentermine and extendedrelease (ER) topiramate (also approved in 2012), and another combination product consisting of ER naltrexone and ER bupropion (approved in late 2014). In Phase III trials of the three products, mean weight reductions ranging from 4.7 to 10.2 kg over periods of one and two years were reported, with substantial percentages of patients achieving weight loss of ≥5%. Adverse effects reported among clinical trial participants were generally mild; however, as the trials excluded patients with significant cardiovascular risks (e.g., uncontrolled hypertension, valvular heart disease), cautious patient selection and monitoring are advised. CONCLUSION.Recently approved medications for longterm management of obesity include lorcaserin, phentermine–topiramate, and naltrexone–bupropion. When these drugs are used to facilitate weight loss, pharmacists can play an important role in helping to ensure appropriate patient selection and monitoring.